Patient‐ versus physician‐reported outcomes in a low‐dose tamoxifen trial in noninvasive breast cancer. Issue 11 (8th October 2021) - Buttiron Webber, Tania; Marra, Domenico; Puntoni, Matteo; Giuliano, Silvia; Briata, Irene Maria; Cevasco, Isabella; Clavarezza, Matteo; D'Amico, Mauro; Defferrari, Carlotta; Gozza, Alberto; Provinciali, Nicoletta; Lazzeroni, Matteo; et al.
Abstract: Background: We recently conducted a de‐escalation trial of low‐dose tamoxifen 5 mg/day ("babytam", BT) or placebo given for 3 years in 500 women with noninvasive breast cancer. Women on babytam had a 52% reduction of recurrence (invasive breast cancer or DCIS) after 5 years. Since menopausal symptoms are major reasons for treatment withdrawal during tamoxifen preventive therapy, we compared and analyzed the patient‐reported outcomes (PROs) with the physician‐reported adverse events and studied their association with recurrence. Methods: Menopausal symptoms recorded by physicians using the Common Terminology Criteria (CTCAEs) were compared with a patient self‐reported validated questionnaire reviewed by a research nurse at baseline and every 6 months up to 36 months. Hot flashes (HF), the main outcome measure, were detected through a self‐report 7‐day diary for frequency and intensity. Treatment adherence and efficacy were assessed by the Kaplan–Meier curves and the Cox model. Results: The number of HF events at 12, 24, and 36 months for PROs versus CTCAEs was 246 versus 12, 238 versus 8, and 210 versus 4, respectively. The majority of events were grade 1. There was no difference in PROs between babytam and placebo except for HF daily frequency, which increased by 1.5 events (95% CI, 1.1–1.8) on placebo to 2.1 on babytam (95% CI, 1.7–2.5, p  = 0.05). The presence of HF at baseline was a favorable prognostic factor for recurrence and a predictive factor for response to babytam. Adherence was similar between babytam and placebo. Conclusions: The use of PROs is effective for identifying frequent mild grade menopausal symptoms which are underestimated by physicians but important prognostic and predictive factors. Research nurse can use these results as a tool to reassure patients about symptoms, improve adherence to treatment, and limit dropouts.